The prevention of depressive symptoms in rural Australian women - Day, Christine; Kane, Robert; Roberts, Clare (Wiley InterScience, 2003)
Two interventions aimed at preventing depressive symptoms in women living in Western Australian rural communities were evaluated against a no-intervention control condition. The standard intervention was based upon traditional cognitive-behaviour treatments for depression; the experimental intervention was based upon prevention strategies derived from the learned helplessness model of depression (e.g. Peterson, Maier, & Seligman, 1993). Seventy-six women were randomly assigned to either the standard or the experimental group, and a further 20 women formed a no-intervention control group. The standard group showed a reduction in depressive symptoms at post-test, but no effects at 6-week or 6-month follow-ups. In contrast, a reduction in depressive symptoms did not appear for the experimental group until the 6-week follow-up at which time a less depressive attributional style was also evident; these effects were even more pronounced at the 6-month follow-up. The no-intervention control group showed no changes across time. It is argued that these results support the applicability of prevention strategies based on the learned helplessness model to this population.